Experiences in Integrating Elements of Cultural Heritage into School Visual Arts Education - Rahimova Gulhayo Qahramonovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the experiences and practices of integrating elements of cultural heritage into visual arts education in general secondary schools. It examines how folk art, historical monuments, national ornaments, traditional crafts, and oral traditions can be effectively used to enhance students’ understanding of cultural identity, aesthetic perception, and creative thinking. The study emphasizes that the incorporation of heritage-based themes in art lessons fosters students’ appreciation of national values, strengthens their aesthetic taste, and cultivates pride in cultural traditions. Furthermore, it highlights the pedagogical strategies, interactive methods, and project-based activities teachers can use to implement this integration successfully. The paper provides practical recommendations for reinforcing moral, aesthetic, and cultural education through art lessons rooted in cultural heritage.